2021
DOI: 10.31234/osf.io/wy2ah
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sibling Bullying in Turkish Adolescents: Translation and Cross-Cultural Validation of the Sibling Bullying Questionnaire

Abstract: Purpose: The primary aim of this study was to translate the Sibling Bullying Questionnaire (SBQ) into Turkish and validate it. A secondary aim was to estimate the prevalence of sibling bullying in Turkish adolescents. Methods: The SBQ was forward and backwards translated by a team of English-Turkish bilinguals. Following this, self-report data were collected from Turkish adolescents (N=301) aged 10 to 18 years old (mean age=14.25 years, SD=2.46). Confirmatory factor analysis (CFA) was used to confirm the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This well aligns with a recent report, as Toseeb, McChesney, Dantchev, and Wolke (2020) have also found that White adolescents are at increased risk of being a victim (i.e., victim‐only) but not a perpetrator (i.e., bully‐only) of sibling bullying. Perhaps, this may be because non‐White families are more inclined to protect their autistic child during sibling conflict and bullying situations than White families (Deniz, Asbury, & Toseeb, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This well aligns with a recent report, as Toseeb, McChesney, Dantchev, and Wolke (2020) have also found that White adolescents are at increased risk of being a victim (i.e., victim‐only) but not a perpetrator (i.e., bully‐only) of sibling bullying. Perhaps, this may be because non‐White families are more inclined to protect their autistic child during sibling conflict and bullying situations than White families (Deniz, Asbury, & Toseeb, 2023).…”
Section: Discussionmentioning
confidence: 99%